Altered Composition of Gut Microbiota in Depression: A Systematic Review - Barandouzi, Zahra Amirkhanzadeh; Starkweather, Angela R.; Henderson, Wendy A.; Gyamfi, Adwoa; Cong, Xiaomei S. (Frontiers in Psychiatry, 2020)
Cumulative evidence shows a linkage between gut microbiota pattern and depression through the brain-gut microbiome axis. The aim of this systematic review was to identify the alterations of the gut microbiota patterns in people with depression compared to healthy controls. A comprehensive literature search of human studies, published between January 2000 to June 2019 were reviewed. The key words included gastrointestinal microbiome, gut microbiome, microbiota, depression, depressive symptoms and depressive disorder. The systematic review adhered to the Preferred Reporting Items for systematic Reviews and Meta-Analysis (PRISMA) guidelines. Nine articles met the eligibility criteria. Disparities in α-diversity and β-diversity of the microbiota existed in people with depression compared to healthy controls. At the phylum level, there were inconsistencies in the abundance of Firmicutes, Bacteroidetes and Proteobacteria. However, high abundance in Actinobacteria and Fusobacteria phyla were observed in people with depression. On the family level, high abundance of Actinomycineae, Coriobacterineae, Bifidobacteriaceae, Clostridiales incertae sedis XI, Porphyromonadaceae, Clostridiaceae, Lactobacillaceae, Streptococcaceae, Eubacteriaceae, Thermoanaerobacteriaceae, Fusobacteriaceae, Nocardiaceae, Streptomycetaceae, and low abundance of Veillonellaceae, Prevotellaceae, Bacteroidaceae, Sutterellaceae, Oscillospiraceae, Marniabilaceae and Chitinophagaceae were observed in people with depression. On the genus level, high abundance of Oscillibacter, Blautia, Holdemania, Clostridium XIX, Anaerostipes, Anaerofilum, Streptococcus, Gelria, Turicibacter, Parabacteroides, Eggerthella, Klebsiella, Paraprevotella, Veillonella, Clostridium IV, Erysipelotrichaceae incertae sedis, Eubacterium, Parvimonas, Desulfovibrio, Parasutterella, Actinomyces, Asaccharobacter, Atopobium, Olsenella and low abundance of Coprococcus, Lactobacillus, Escherichia/Shigella, Clostridium XlVa, Dialister, Howardella, Pyramidobacter and Sutterella were found in people with depression. Alteration of gut microbiome patterns is evident in people with depression. Further evidence is warranted to allow for translation of microbiome findings toward innovative clinical strategies that may improve treatment outcomes in people with depression.